Adenoviral nephritis in a renal transplant recipient: Case report and literature review. Issue 4 (17th July 2017) - Veer, Manik; Abdulmassih, Rasha; Como, James; Min, Zaw; Bhanot, Nitin
Abstract: Adenovirus (AdV) infections in transplant recipients may cause invasive disease. We present a case of granulomatous interstitial nephritis secondary to AdV infection in a renal transplant recipient that was initially interpreted as acute graft rejection on histopathology. Specific testing based on clinical suspicion, however, aided in making an accurate diagnosis. We present a retrospective review of all cases of AdV infection in renal transplant recipients to date, and analyze outcomes based on different treatment modalities for this disease.